ANALISISPENGELOLAAN RETRIBUSI PASAR UNTUK MENINGKATKAN PELAYANAN PUBLIK (Studi Pasar Brang Biji Sumbawa Tahun 2020) - I Ismawati; Ika Fitriyani; Arya Dessana Putra (Pusat Riset dan Publikasi, 2021)
This research is a field research located in the district of Sumbawa Besar which aims to determine the management of market fees to improve public services. The case study of the Sumbawa Brang Seed Market in 2020. The formulation of the problem in this study is how to manage market fees to improve public services in the Sumbawa Seed Brang Market. , the perception of the sword on the management of user fees to improve public services in the Seed Brang market, as well as the supporting and inhibiting factors for the results of the market retribution management in improving public services in the Brang Seed market. The data sources of this study used primary and secondary data using 4 informants from the market management office, market head, traders, and buyers. The results of this study indicate that the management of market retribution to improve public services in the bran seed market has not been running optimally. This can be seen from the lack of facilities and infrastructure provided by the management and government and there is no guarantee given to market service users. As for the responsiveness problem, the management and government are quite good at maximizing the existing potential. The traders are quite satisfied with what they have received so far although there is something that needs to be improved. The supporting factors that make public services in the bran seed market quite good are the responsive and friendly attitude of the officers, as well as good awareness from the management and users of market services. while the inhibiting factors are the limited rights and authority of the government management in meeting market needs and the government's lack of attention to market service users.